Pengaruh Aplikasi Digital Point Of Sales (DIGIPOS) Terhadap Perilaku Konsumen Variabel Effort Expectancy Model Unified Theory Of Acceptance And Use Of Technology (UTAUT) Studi Kasus Telkomsel Bogor - Syarif, Usman; Djamil, Masyhudzulhak; Ramly, Amir Tengku (Jurnal Manajemen, 2020)
The telecommunications industry business in Indonesia in recent years has changed drastically from voice and SMS services to digital services. This change requires Telkomsel as one of the cellular companies in Indonesia to also transform into a digital company, one of which is the transformation in the field of Channel Management, by introducing the Digipos application in 2017. The implementation in the field of Digipos has not been used massively by outlets, especially in the city of Bogor where this research was conducted. This research uses a quantitative approach with descriptive and causal research methods. Data were collected through literature studies and questionnaires with analytical techniques using PLS and Descriptive Analysis. Based on PLS analysis, one of the four variables namely Effort Expectancy (EE) has a positive influence on the Use Behavior to use Digipos. The level of ease of using the system, perceived to be quite good, is seen from the average index with a fairly high adoption rate. From the analysis of PLS Effort Expectancy (EE) has a positive influence on customer behavior.